Laser Interstitial Thermal Therapy (LITT) in Brain Tumors: A Narrative Review - Abdulrahman H. Alashkar; Hassan M. Ahmed; Mohammad A. Aljawash; Bahaeddin Muhsen (Dr. Sulaiman Al Habib Medical Journal)
Laser interstitial thermal therapy (LITT) emerged in 1990 as a promising treatment for brain tumors. It is a minimally invasive procedure that has many advantages over conventional craniotomy and has various applications in the management of brain neoplasms. It has been used in the treatment of radiation necrosis, glioblastoma multiforme, metastatic brain tumors, and posterior fossa tumors. Two main LITT platforms are available commercially in the United States: the Visualase system and the Monteris NeuroBlate platform. LITT has become increasingly popular in recent years due to its preciseness and minimal invasiveness. In this review, we scope the literature for the use of LITT in brain tumors, and we present a sample of studies that addressed its applications in this area.